3D bioprinted autologous bone particle scaffolds for cranioplasty promote bone regeneration with both implanted and native BMSCs. (14th March 2023) - Huan, Yu; Zhou, Dezhi; Wu, Xiuquan; He, Xin; Chen, Hongqing; Li, Sanzhong; Jia, Bo; Dou, Yanan; Fei, Xiaowei; Wu, Shuang; Wei, Jialiang; Fei, Zhou; et al.
Abstract: Although autologous bone (AB) grafting is considered to be the gold standard for cranioplasty, unresolved problems remain, such as surgical-site infections and bone flap absorption. In this study, an AB scaffold was constructed via three-dimensional (3D) bedside-bioprinting technology and used for cranioplasty. To simulate the skull structure, a polycaprolactone shell was designed as an external lamina, and 3D-printed AB and a bone marrow-derived mesenchymal stem cell (BMSC) hydrogel was used to mimic cancellous bone for bone regeneration. Our in vitro results showed that the scaffold exhibited excellent cellular affinity and promoted osteogenic differentiation of BMSCs in both two-dimensional and 3D culture systems. The scaffold was implanted in beagle dog cranial defects for up to 9 months, and the scaffold promoted new bone and osteoid formation. Further in vivo studies indicated that transplanted BMSCs differentiated into vascular endothelium, cartilage, and bone tissues, whereas native BMSCs were recruited into the defect. The results of this study provide a method for bedside bioprinting of a cranioplasty scaffold for bone regeneration, which opens up another window for clinical applications of 3D printing in the future.